Critiquing the response to the Ebola epidemic through a Primary Health Care Approach - Vera Scott; Sarah Crawford-Browne; David Sanders (BMC, 2016)
Abstract Background The 2014/2015 West Africa Ebola epidemic has caused the global public health community to engage in difficult self-reflection. First, it must consider the part it played in relation to an important public health question: why did this epidemic take hold and spread in this unprecedented manner? Second, it must use the lessons learnt to answer the subsequent question: what can be done now to prevent further such outbreaks in the future? These questions remain relevant, even as scientists announce that the Guinea Phase III efficacy vaccine trial shows that rVSV-EBOV (Merck, Sharp & Dohme) is highly efficacious in individuals. This is a major breakthrough in the fight against Ebola virus disease (EVD). It does not replace but may be a powerful adjunct to current strategies of EVD management and control. Discussion We contribute to the current self-reflection by presenting an analysis using a Primary Health Care (PHC) approach. This approach is appropriate as African countries in the region affected by EVD have recommitted themselves to PHC as a framework for organising health systems and the delivery of health services. The approach suggests that, in an epidemic made complex by weak pre-existing health systems, lack of trust in authorities and mobile populations, a broader approach is required to engage affected communities. In the medium-term health system development with attention to primary level services and community-based programmes to address the major disease burden of malaria, diarrhoeal disease, meningitis, tuberculosis and malnutrition is needed. This requires the development of local management and an investment in human resources for health. Crucially this has to be developed ahead of, and not in parallel with, future outbreaks. In the longer-term a commitment is required to address the underlying social determinants which make these countries so vulnerable, and limit their capacity to respond effectively to, epidemics such as EVD. Conclusion The PHC approach offers an insightful critique of the global and regional factors which have compromised the response of health systems in Guinea, Liberia and Sierra Leone as well as suggesting what a strengthened EVD response might involve in the short, medium and long-term.